Ecoturismo e acessibilidade, uma trilha em libras: relato de experiência de uma acadêmica de turismo - Sousa, Thamyres Alves de (Universidade Federal do Tocantins, 2021)
The present work reports the experience of planning and offering an interpretive trail for a group of deaf people. The route chosen for the activity was the trail that leaves the urban area of areas until the Cachoeira da Antiga Usina. The objectives were to identify what assessment this group makes about the quality and accessibility of tourist services for deaf people and the group's impressions about participation in the interpretive trail. A questionnaire was applied to deaf participants as an instrument for data collection. The results showed that social inclusion within the tourist activity is still outdated, requiring improvements in terms of physical, professional and mainly communication structure. In this context, the participants identified the importance of the Brazilian Sign Language - LIBRAS in the tourist activity, so that the deaf person can gain access to the different segments of tourism. Evidencing that the presence of an interpreter in LIBRAS, would be enough to meet the interests of the deaf person. The participants felt excited about the proposed activity, being the first opportunity for interpretive activity directed at the deaf, highlighting the use of the Brazilian Sign Language-LIBRAS to conduct the proposed activity on the interpretive trail.